PENGARUH MODEL QUANTUM TEACHING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SD - Meysi Damayanti; Regina Sipayung; Ester Julinda Simarmata; Patri Janson Silaban (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article describes a research result regarding the effect of the Quantum Teaching model on students’ learning outcomes. The method used in the research was a quantitative experimental research method. The population of the research involved 31 fifth-grade elementary school students of SDN 105327 Perdamean Tanjung Morawa in the academic year 2020/2021. The pretest learning results obtained an average score of 66.96 with enough categories. After the researchers applied the treatment in the experimental class by using the Quantum Teaching model, the researchers, hereafter, provided a post-test and obtained an average score of 83.06 in the category of very good. The results of data processing and the significant value of the Quantum Teaching model obtained were 0.200 > 0.05, whilst the significant value of students’ learning outcomes was 0.200 > 0.05. Based on the calculation, it can be seen that the significant value of the Quantum Teaching model and students’ learning outcomes was higher than 0.05; thus, the students’ learning outcomes were normally distributed. From the results of the research hypothesis testing (t-test), it showed that the Quantum Teaching model had a positive and significant effect. It was proven from the tcount > ttable with significance value of 6.023 > 1.697. Thus, Ha was accepted, which meant that there was a significant influence between the Quantum Teaching (X) model and students’ learning outcomes (Y).